(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Wire cut electrical discharge machining (WCEDM) extensively used in machining of conductive materials when precision of prime importance. Rough cutting operation in WCEDM is treated as challenging one because improvement of more than one machining performance measures viz. metal removal rate (MRR) surface finish (SF) and cutting width (kerf) are sought to obtain a precision work. Using Taguchi’s parameter design significant machining parameters affecting the performance measures are identified as discharge current, pulse duration, pulse frequency, wire speed, wire tension and dielectric flow. It has been observed that a combination of factor for optimization of each performance measure is difficult. In this study, the relationship between control factor and responses like MRR, SF and kerf are established by means of nonlinear regression analysis, resulting in a valid mathematical method. Finally, genetic algorithm, a popular evolutionary approach, is employed to optimize the wire cut electrical discharge machining processwith multiple objectives. This study demonstrates that the WCEDM process parameters can be adjusted to achieve better metal removal rate, surface finish and cutting width simultaneously.